Experimental chemotherapy-induced skin necrosis in swine. Mechanistic studies of anthracycline antibiotic toxicity and protection with a radical dimer compound. - S D Averbuch; M Boldt; G Gaudiano; J B Stern; T H Koch; N R Bachur (The Journal of Clinical Investigation, 1988)
The reactivity of antitumor anthracycline and mitomycin C antibiotics with the oxomorpholinyl radical dimers, bi(3,5,5-trimethyl-2-oxomorpholin-3-yl) (TM3) and bi(3,5-dimethyl-5-hydroxymethyl-2-oxomorpholin-3-yl) (DHM3), was studied in vitro. The oxomorpholinyl radical reduced daunorubicin to a quinone methide intermediate that reacted with solvent to form 7-deoxydaunorubicinone. The solvolysis reaction followed first order kinetics, and the reactivity rate constants (k2) measured for seven anthracycline analogues ranged from 2 X 10(-2) s-1 to 8.0 X 10(-4) s-1. The chemical reactivity of each anthracycline quinone methide correlated with the total skin toxicity caused by the respective parent anthracycline following injection into swine skin. Microscopic examination of experimental lesions in swine skin resemble those observed in humans after inadvertant chemotherapy extravasation. Hydrocortisone sodium succinate was not effective for the treatment of doxorubicin-induced skin necrosis, whereas DHM3 was effective for the treatment of skin necrosis caused by all seven anthracyclines and by the quinone containing antibiotic, mitomycin C. Images